2019
DOI: 10.1590/2447-536x.v25i4.2046
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture and greenhouse acclimatization of Oncidium varicosum (Orchidaceae) with microorganisms isolated from its roots

Abstract: Sustainable production of orchids may be achieved with the use of symbiotic microorganisms that improve resistance of plants to pests and diseases and reduce the need of substrate fertilization. In this study, one fungus (F1), one yeast (Y1) and one gram-positive bacteria (B+) were isolated from the roots of the orchid Oncidium varicosum and used in the cultivation of protocorms and plantlets obtained from seeds of this species. Cultivation of protocorms in Murashige and Skoog (MS) medium enriched with sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…The in vitro germination of some species, such as Maclura tinctoria, Cocos nucifera, and Syagrus coronata, has been increased by supplying the medium with GA 3 (Gomes et al, 2010;Medeiros et al, 2015;Montero-Cortés et al, 2011). This growth regulator could be important for cell growth and elongation, leaf expansion and photosynthetic processes, as well as for the activity of important metabolic enzymes, such as nitrate reductase (Gupta;Chakrabarty, 2013, Bezerra et al, 2019. Enhancement of nitrate reductase activity may be beneficial, since this enzyme is responsible for the assimilation of nitrogen, an essential element found in many macromolecules and components of secondary metabolism, including proteins, nucleic acids, cell wall components, hormones, and vitamins (Krapp, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro germination of some species, such as Maclura tinctoria, Cocos nucifera, and Syagrus coronata, has been increased by supplying the medium with GA 3 (Gomes et al, 2010;Medeiros et al, 2015;Montero-Cortés et al, 2011). This growth regulator could be important for cell growth and elongation, leaf expansion and photosynthetic processes, as well as for the activity of important metabolic enzymes, such as nitrate reductase (Gupta;Chakrabarty, 2013, Bezerra et al, 2019. Enhancement of nitrate reductase activity may be beneficial, since this enzyme is responsible for the assimilation of nitrogen, an essential element found in many macromolecules and components of secondary metabolism, including proteins, nucleic acids, cell wall components, hormones, and vitamins (Krapp, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation is the most common method used for large-scale cloning ornamental horticulture plant species (Kumari et al, 2017;Naidoo et al, 2017;Bezerra et al, 2019). Among the ornamental species frequently micropropagated are bromeliads.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria have also exhibited good potential for application in orchid cultivation. In this sense, Bezerra et al (2020) reported positive impact of the application of rooting-derived microorganisms, especially bacterial isolate in the in vitro culture and plantlet acclimatization of Oncidium varicosum. In vitro bacterization of photinia (Photinia × fraseri Dress), another ornamental FIGURE 4 | Schematic summary of some benefits of biotization process compared to classical micropropagation process.…”
Section: Application In Agriculture Horticulture and Forestrymentioning
confidence: 99%
“…An effective system for the in vitro propagation of orchids must integrate the associated symbiotic fungi through biotization approach. This will allow good micropropagation and acclimatization with no apparent “transient transfer shock.” In addition, the technique of biotization could be a realistic way to produce low-cost micropropagated plantlets ( Bezerra et al, 2020 ). Some bacteria have also exhibited good potential for application in orchid cultivation.…”
Section: Application In Agriculture Horticulture and Forestrymentioning
confidence: 99%